PROSES PERALIHAN TANAH ULAYAT MENJADI HAK GUNA USAHA OLEH PT. MUTIARA AGAM KABUPATEN AGAM - Sumardi, Tiara (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The definition of Communal land according to6thLocal Regulation in 1starticle 7th verseon 2008 about Communal land and its utilization is a heritage land with the natural resources over and in it, obtained herediterary and also a part of tradition law society rights in West Sumatera Province. Cultivation Rights Land define by 28th article 1st verse in Basic Agrarians Principles is the rights to cultivates the land that directly managed by its state within certain period of timefor agriculture, fishery and farms Incorporates, as it is mentioned in 29th article of the principles.The policy to take over the land ownershipis related withthe regulation of the takingover land process owned by society or individuals by states or individuals or other groups of society. This taking over process has a correlation with the utilization of the land for contruction purpose such as roads, residentials, industries, trading areas etc and also correlates with readjustment of the land utilization, ownership and authorizationin line with land usefulness. This research was done to Mutiara Agam Inc in Nagari Tiku Limo Jorong Tanjung Mutiara District, Agam Regency. The Problems of the research are first, how do the process of taking over communal land into cultivation rights land? Second, what are the benefits of this process for the owner of communal land? Third, How do the status of communal land when it tranforms into cultivation rights land and after the agreement end? This research was conducted with juridical empiric method. The result of this research shows that the land utilized by Mutiara Agam Inc as cultivation rights land is used to be communal land owned by society and the agreement will end on December 31th, 2026. The agreement was listed in Injuction of the head of National Land Agency number : 14/HGU/1991 about the cultivation right land given to Mutiara Agam Inc. The benefit for the society of Nagari Tiku Limo is the giving of 3000 hectares land by Mutiara Agam Inc as plasm partnership that will be managed by society. The status of the communal land right now is as the cultivation right land and if this agreement ends, the status will be back into the former status after re-negotiation.